CLASSIFICATION AND TYPOLOGY OF URBAN SETTLEMENTS OF UKRAINE - Поручинський, Володимир; Сосницька, Ярослава (Human Geography Journal, 2015)
Essence of the systems of settling apart and settlements is considered in this article. The essence of concepts «town», «settlement» and «agglomeration» as basic forms are reveal. The analysis of existent classifications and typologies urban point by different criterion. To propose scheme which represent classification towns by population, historical-genetic, functional and planning structures. Particularity any elements typological structure is describe. It is defined to which types and classes it is possible to take a towns Ukraine.